MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM GERAK MANUSIA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS-GAMES-TOURNAMENTS (TGT) - Meri Rahmida (Universitas Lambung Mangkurat, 2011)
The research on human motion system class using cooperative learning model types of “TGT” method was conducted. This study aims to find out students 'improvement, student’s activities and responses on “TGT” method. This research used class-action-research design with 2 cycles, each cycle consisting of two meetings. Research subjects is 8th grade student of SMPN 1 Banua Lawas, totaling 27 people. The data was collected by observation, giving the test, deployment questionnaire. The data obtained were analyzed by qualitative descriptive. The results showed that (1) the ability of teachers in the first cycle in implementing design of learning (RPP) was 97.82% in the category of pretty good and the second cycle teachers can implement the learning design was 100% good category, (2) student learning activities in the first cycle, active students on average of 96.29% and the students who are active in the second cycle an average of 97.23%, (3) student learning outcomes in the first cycle average of 71.48 and 85.18% classical mastery learning and the second cycle has increased to 77.59 with a classical mastery learning 96.30%; (4) student responses to learning activities is positive. Key word: TGT, reflection, human motion system, science in junior high school, respond